Perancangan Pabrik MTBE ( Metil Tertiari Butil Eter ) Dari Metanol Dengan Desain Alat Utama Menara Distilasi Metanol Recovery Tower - Atsarina, Aufa Zakya; Amraini, Said Zul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Human life will not be separated from vehicles as a medium of transportation that makes it easier to move from one place to another. Until now, oil is the largest percentage of vehicle fuel providers. One of the important components in fuel from petroleum is additives. The addition of additives can produce fuel with a higher octane function as a booster, and also enhances the combustion of fuel by the vehicle engine. The type of additive used in most countries is methyl tert butyl ether (MTBE). MTBE is produced from a catalytic reaction that occurs between methanol and isobutene which will be produced with a capacity of 280,000 tons / year. One of the supporting tools for producing MTBE is a distillation tower, namely the methanol recovery tower.This distillation tower will separate the methanol that is still mixed with water from the previous operation unit so that the methanol can be recovered. Distillation tower is designed with feed, distillate and bottom temperatures of 357 K, 329 K and 372 K and feed, distillate and bottom flow rates of 14,207 kg / hour, 11,812 kg / hour and 2394 kg / hour. The results of the design obtained the distillation tower diameter and height of 5.28 m and 17.86 m with the number of trays is 35 pieces. The overall process to produce MTBE requires one fixed bed multitubular reactor, one mixer, four distillation units, three heat exchangers (one double pipe type and two shell and tube types), 2 heaters units (shell and tube), 2 coolers (double pipe), 3 centrifugal pumps with 5 storage tanks. The amount of Fixed Capital Investment (FCI) is $ 39,009,534. The amount of Direct Cost (DC) is $ 17,571,862 and Indirect Cost (IC) is $ 21,437,671. The Working Capital Investment (WCI) fee is $ 6,884,035 and the Total Capital Investment (TCI) fee is $ 45,893,569. The value of the Break Even Point (BEP) is 50%. The amount of Return On Investment (ROI) is 52%, Pay Out Time (POT) is 1.5 years, Shut Down Point (SDP) is 0.1% and the Internal Rate of Return (IRR) is 22.76%. The most sensitive factors that can affect the feasibility of this project are the selling price of the product and the volume of production. So that based on the analysis that has been done, it can be concluded that the factory is feasible to build. Keywords: Methyl Tert Butyl Ether, Methanol, Net Profit After Tax.